Influence of Perifiton Substrate Density on Growth, Survival Rate, and Biomass Gain of Vannamei Shrimp (Litopenaeus vannamei) in Ponds - Andi Adam Malik; Sahabuddin Sahabuddin; Yushra Yushra; Abdul Asis Bahri (Indonesian Journal of Limnology, 2023)
This study aims to determine the effect of periphyton substrate density on growth, survival rate, and biomass gain of vannamei shrimp (Litopenaeus vannamei) in ponds. This study was conducted from February 1, to March 31, 2023 at the traditional ponds in Lawallu Village, Soppeng Riaja Subdistrict, Barru Regency, South Sulawesi Province. The test animal used were vannamei shrimp seeds (PL 17–20) stocked at a density of 50 individual/m2. Completely randomized design was used, with 4 treatments and 3 replications for each treatment. The parameters observed were weight and length gain, survival rate, and biomass gain. At the end of rearing, the average weight gain in each treatment were A (3.4 g), B (3.8 g), C (4.1 g), and D (4.7 g); the average length gain in each treatment were A (3.2 cm), B (5.4 cm), C (5.97 cm), and D (6.97 cm); the average survival rate in each treatment were A (83%), B (89%), C (90%), and D (94%); and the average biomass gain in each treatment were A (287 g/m2), B (335 g/m2), C (372 g/m2), and D (443 g/m2). Periphyton substrate density has significantly affected the growth and biomass gain of vannamei shrimp seeds. The highest growth, survival rate, and biomass gain were obtained at treatment D, namely using periphyton substrate at a density of 15 bamboos/m2.